ENHANCING ENGLISH SPEAKING SKILL THROUGH JIGSAW COOPERATIVE LEARNING (Action Research In X Class of MIA SMA Negeri 2 DKI Jakarta) - Khaessar Indra Perkasa; Emzir Emzir; Ratna Dewanti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
Abstract Many factors make quality education or not. These factors include the professionalism of educators, educational inputs both in the form of student input and facilities (infrastructure input), learning process, environment and others. This paper attempts to confirm the process of improving students' speaking skills on English subjects through cooperative learning of Jigsaw models on students in X Class of MIA SMA Negeri 2 DKI Jakarta. The subjects were 108 students studying speaking English The subjects then were randomly assigned into experimental group and control group The experiment lasted for nine weeks started with pre-test in the beginning and ended with a post - test in the last meeting. During the treatment, the teacher applied planning, drafting, revising and editing stages in learning. The result shows Learning outcomes in students, especially speaking skills in students in SMA Negeri 2 DKI Jakarta has increased. This is evident through the experiments on cycles I and II both for class 10 Mipa 1, from the mean of 70.9167 to 84.2778. class 10 Mipa 2, from the average 71.8056 to 86.2222 and for class 10 Mipa 3 from the average 70.5833 to the average 84.2222 so that the total increase during applying the Jigsaw type cooperative learning model from the initial value. Keywords: skill speaking english, jigsaw cooperative learning